Cancer of the testis - Laguna, Pilar; Albers, Peter; Bokemeyer, Carsten; Richie, Jerome P. (Springer, 2011)
Cancer of the Testis presents a thorough account of every aspect of this disease, including histology, risk factors, prognosis, clinical presentation, diagnosis and treatment. Additionally, there is a focus on the pertinent issues of fertility, late effects of primary therapy, follow-up after primary treatment and testicular cancer in childhood. With an international authorship comprised of many of the key contributors to the field, this book brings together a rich and balanced range of perspectives. A state-of-the-art reference volume on testicular cancer, this book is essential reading for urologists, medical oncologists and radio-oncologists. M. Pilar Laguna, MD PhD, is an Associate Professor in Urology at the University of Amsterdam, The Netherlands. Peter Albers, MD, is Chairman of the Department of Urology at Dusseldorf University, Germany. Carsten Bokemeyer, MD, is Director of Oncology and Hematology at Hubertus Wald Tumorzentrum at the University Medical Center in Hamburg, Germany. Jerome P. Richie, MD, is the Elliot C. Cutler Professor of Urologic Surgery at Harvard Medical School and Chief of Urology at Brigham and Women's Hospital in Boston, USA.